The church of the dead : the epidemic of 1576 and the birth of Christianity in the Americas - Hughes, Jennifer Scheper (North American religions., 2021)
"In 1576 a catastrophic epidemic devastated Indigenous Mexican communities and left the colonial church in ruins. With its horrific final symptom of hemorrhage from the nose, the unfamiliar disease, which the Nahua named cocoliztli, took almost two million lives. In the crisis and its immediate aftermath, Spanish missionaries and surviving pueblos de indios held radically different visions for the future of church in the Americas"--